Can a Home‐based Cardiac Physical Activity Program Improve the Physical Function Quality of Life in Children with Fontan Circulation?. (16th February 2016) - Jacobsen, Roni M.; Ginde, Salil; Mussatto, Kathleen; Neubauer, Jennifer; Earing, Michael; Danduran, Michael
Abstract: Objective: Patients after Fontan operation for complex congenital heart disease (CHD) have decreased exercise capacity and report reduced health‐related quality of life (HRQOL). Studies suggest hospital‐based cardiac physical activity programs can improve HRQOL and exercise capacity in patients with CHD; however, these programs have variable adherence rates. The impact of a home‐based cardiac physical activity program in Fontan survivors is unclear. This pilot study evaluated the safety, feasibility, and benefits of an innovative home‐based physical activity program on HRQOL in Fontan patients. Methods: A total of 14 children, 8–12 years, with Fontan circulation enrolled in a 12‐week moderate/high intensity home‐based cardiac physical activity program, which included a home exercise routine and 3 formalized in‐person exercise sessions at 0, 6, and 12 weeks. Subjects and parents completed validated questionnaires to assess HRQOL. The Shuttle Test Run was used to measure exercise capacity. A Fitbit Flex Activity Monitor was used to assess adherence to the home activity program. Results: Of the 14 patients, 57% were male and 36% had a dominant left ventricle. Overall, 93% completed the program. There were no adverse events. Parents reported significant improvement in their child's overall HRQOL ( P < .01), physical function ( P < .01), school function ( P = .01), and psychosocial function ( P < .01). Patients reported no improvement in HRQOL. Exercise capacity, measured by total shuttles and exercise time in the Shuttle Test Run and calculated VO2 max, improved progressively from baseline to the 6 and 12 week follow up sessions. Monthly Fitbit data suggested adherence to the program. Conclusion: This 12‐week home‐based cardiac physical activity program is safe and feasible in preteen Fontan patients. Parent proxy‐reported HRQOL and objective measures of exercise capacity significantly improved. A 6‐month follow up session is scheduled to assess sustainability. A larger study is needed to determine the applicability and reproducibility of these findings in other age groups and forms of complex CHD.